DESAIN SISTEM PAKAR IDENTIFIKASI PENYAKIT TANAMAN HORTIKULTURA UNTUK MEMPERMUDAH PENANGGULANGAN HAMA - Dian Nathasia, Novi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Expert System is an Artificial Intelligent system that combines a database with niferensi system. Expert systems can be implemented into various areas of agriculture one of the study aims to create a system that represents a specialist in identifying diseases of horticultural crops as well as control measures based on physical characteristics of plants. The expert system is expected to help farmers in pest control so that crop failure due to pests can be minimized. The design of Expert System draws from existing systems and data used are already using data from experts, is intended for the validity of the diagnosis.The software for this expert system designed by using Borland Delphi 7.0 programming Windows-based, as adapted to the changing times. Besides, it is also easier for the operator to operate the application, because basically the way the operation using the Windows operating system. Keywords: Expert Systems, Horticulture Plant Disease